Experience with Budgetary Convergence in the WAEMU - Masson, Paul (IMF Working Papers; Working Paper ;, 2002)
This paper reviews the experience of fiscal adjustment undertaken in the West African Economic and Monetary Union (WAEMU) countries since the entry into force of the 1994 treaty establishing the framework for a regional convergence of national fiscal policies. We propose a measure of the structural deficit that corrects for movements of both the business cycle and terms of trade. Though the fiscal deficit worsened in 1998-2001 in some countries because of terms of trade deterioration and unfavorable movements in the business cycle, convergence stalled even when corrected for these factors. Meeting fiscal deficit targets in the future will be facilitated by a favorable external environment but, in any case, will require a higher revenue ratio and downward pressure on government wages as shares of GDP.